The prohibition of mercenarism and the prohibition and regulation of private security and military services in areas of armed conflict with specific reference to South Africa : 1994–2007 - Hough, Mike (Michael) (University of Pretoria, 2013)
Thesis (DPhil (Political Sciences))--University of Pretoria, 2012.